2013
DOI: 10.1088/0957-0233/24/7/075203
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for a fibre Bragg grating interrogation system utilizing an arrayed waveguide grating for dynamic strain measurement

Abstract: Dynamic strain signals are important for many structural monitoring applications, but the high-speed interrogation of strain sensors based on fibre Bragg gratings (FBGs) remains a challenge. Arrayed waveguide grating (AWG) interrogation schemes have been proposed, and by using modelling and validation experiments several design considerations are investigated and their relationship to system performance indicators determined. The Bragg grating length has an impact on the ability of the grating to ‘observe’ the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…These values reduce in a huge way the cost of the system of interrogation. The proposed filter serves to eliminate the problems mentioned above and make a challenge with the arrayed waveguide grating [18] and the Fabry Perot cavity [19]. In addition, the edge filter for the interrogation system must be accordable and provide for each channel of FBG sensors an individually filter with a midband bandwidth.…”
Section: Midband Filtermentioning
confidence: 99%
“…These values reduce in a huge way the cost of the system of interrogation. The proposed filter serves to eliminate the problems mentioned above and make a challenge with the arrayed waveguide grating [18] and the Fabry Perot cavity [19]. In addition, the edge filter for the interrogation system must be accordable and provide for each channel of FBG sensors an individually filter with a midband bandwidth.…”
Section: Midband Filtermentioning
confidence: 99%
“…Yuan et al demonstrated an AWG system that increases the channel spacing to 3 nm, and the dynamic range was 1.2 nm with a 1.3 nm bandwidth at 3 dB 18 . In the above studies, the dynamic range is still limited by the bandwidth of a single channel in the AWG and the small wavelength interval between two intersecting AWG channels 21 , so the dynamic range of previous demodulation methods was not large. Considering the correlation between the dynamic range and the relative spectral width of the FBG and AWG channels, a scheme for measuring the power of multiple channels is proposed to improve the dynamic range and remove the constraint of channel spacing 22,23 , but the peak of the FBG must overlap with several AWG channels.…”
Section: Introductionmentioning
confidence: 99%
“…The typical static resolution of such sensors is in the order of 2-4 microstrain (2.5-5 pm) [1], and the best value reported is 0.04-0.05 pm [3], [4]. Recently several approaches to use photonic integration to reduce the size and cost of the units were made [5]. The achieved resolution expressed as an RMS wavelength measurement noise σ λrms ranges from half a picometer [6] to a few picometers [7].…”
Section: Introductionmentioning
confidence: 99%